Passive mode-locking through nonlinear polarization rotation in low-birefringence fibers - Chang, CW; Chi, S (My University, 1997)
A numerical model for the generation of ultrashort soliton pulses from erbium-doped fiber ring lasers is presented. The model is used to study the pulse dynamics of a simple cavity configuration that uses a low birefringence fiber combined with crossed polarizers. Simulations show that stable pulses with a FWHM as short as 70 fs can be generated. It is also shown that coherent coupling may enhance mode-locking in a weakly linearly birefringent fiber under optimum operation conditions, and in certain cases a period doubling bifurcation occurs due to residual linear birefringence in the fibers.
Keywords: fiber laser; mode-locking; nonlinear polarization rotation